Factors Associated With The Incidence Of Low Birth Weight (Lbw) In The Work Area Of Public Health Center Beruntung Raya Banjarmasin City In 2016-2017 - Fitria, Amalia Rizky (JURNAL KEBIDANAN BESTARI, 2022)
The result of SUPAS 2015 shows the Infant Mortality Rate (IMR) in Indonesia of 22,23 per 1.000 births. Factors that affect the occurrence of LBW is the factors of mother include age, parity, birth spacing and pregnancy complications. The incidence of LBW in the Puskesmas Beruntung Raya was fluctuation, in 2015 (4,7%), in 2016 (5,55%) and in 2017 (3,27%) and infant mortality (5,0%). This study aims to determine the correlation between age, parity, birth spacing and pregnancy complication with the occurrence of LBW in Work Area Puskesmas Beruntung Raya Banjarmasin City In 2016-2017. This research method used analytical survey with case control approach. The population is all newborns are not the first child and born aterm 259 people. Samples cases:samples control, 1:2 ratio 15 all LBW:30 who did not experience LBW using Systematic Random Sampling. The instrument research use the register book of birth, cohort of pregnant women and medical record respondence in 2016-2017. Data analysis using Chi Square with α 0,05. The result of were 15 people (33,3%), 12 unsafe age (26,7%), unsafe parity (11,4%), unsafe 10 birth spacing (22,2%), had 21 complications (46,7%). Chi Square statistical test results for age ρ value 0,49, parity ρ value 0,72, birth spacing ρ value 0,01, and pregnancy complication ρ value 0,00. The value of ρ < α means there is a correlation between the factors studied with the incidence of LBW. The conclusion of this study that there is no correlation between maternal age and parity with the occurrence of LBW and there is a correlation between birth spacing and pregnancy complication with LBW occurrence.